Young, Munson and Okiishi's A brief introduction to fluid mechanics - Young, Donald F.; Okiishi, T. H. (Theodore Hisao) 1939-; Muson, Bruce R.; Hochstein, John I.; Gerhart, Andrew L. (John Wiley & Sons Singapore Pte. Ltd., 2021)
Young, Munson and Okiishi's A Brief Introduction to Fluid Mechanics is designed to cover the standard topics in a basic fluid mechanics course in a streamlined manner that meets the learning needs of students better than the encyclopedic style of traditional texts. The text lucidly presents basic analysis techniques and addresses practical concerns and applications with a strong visual approach. This approach helps students connect the math and theory to the physical world and practical applications and apply these connections to solving problems. This adapted edition of the book comes with updates that clarify, enhance, and expand certain ideas and concepts. It includes new sections on Finite Control Volume Analysis, Compressible Flow, Equilibrium of Moving Fluids, Most Efficient Channel Section. The new examples and problems build upon the understanding of engineering applications of fluid mechanics and the edition has been completely updated to use SI units.